Evaluation of Osteoarticular Involvement Associated with Brucellosis in Children - Tuğba Nur Kutlu Beşeren; Zafer Bıçakçı; Müferet Ergüven; Hayrunnisa Bekis Bozkurt (Düzce Tıp Fakültesi Dergisi)
Aim: Brucellosis is a significant public health problem with high morbidity. Its most frequent complication is osteoarticular involvement. The study aimed to evaluate the relationship of osteoarticular involvement with clinical features and prognosis in children with brucellosis.Material and Methods: This retrospective study included pediatric patients between the ages of 1 and 18 years who were hospitalized and diagnosed with brucellosis between 2015 and 2020, and were regularly followed up. and all their findings and osteoarticular involvement data within the last two years were recorded. Clinical features, laboratory findings, osteoarticular involvement, and relapse rates of the patients were evaluated.Results: A total of 80 patients were included study. During the follow-up period, relapse developed in 14 (17.5%) patients. The most commonly affected joints were right (40%, n=32) and left (26.3%, n=21) hips, then right (27.5%, n=22) and left (23.8%, n=19) knees. Shoulder joint involvement rates and C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), alanine transaminase (ALT), and aspartate aminotransferase (AST) levels were statistically significantly higher in the relapse group (p=0.016, p=0.003, p=0.001, p